The synthesis of ethene during the oxidative coupling of methane - Burch, R; Dost, A; Rice, D; Tsang, S; Webb, G (Baltzer Science Publishers, Baarn/Kluwer Academic Publishers, 1989)
The effect of residence time on the selectivity of a MgO catalyst for the formation of ethene in the methane coupling reaction has been studied. It is found that the variation in ethene selectivity with this time follows opposite trends depending on the experimental conditions. In both cases the results show a positive intercept at zero residence time which may indicate that ethene is a primary product. However, calculations show that gas phase radical reactions just above the catalyst surface could account for the ethene observed even at very short residence times. It is concluded that experiments such as these cannot reliably distinguish between primary and secondary product formation. A SmOCl catalyst was studied and it was found that HCl was released when wet gases were passed over the catalyst at relatively low temperatures. It is concluded that much of the ethene produced over oxychloride catalysts may be produced by gas phase reactions involving chlorine radicals. © 1989 J.C. Baltzer A.G. Scientific Publishing Company.